STRATEGI PENGEMBANGAN POTENSI DESA DALAM KERANGKA OTONOMI DAERAH - Lailiyah, Kusroh (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2024)
This research aims to determine village potential development strategies within the framework of regional autonomy. This research uses a qualitative approach through descriptive analysis methods based on literature studies obtained which are then used as analysis material. The results of this research show that there are several strategies that can be implemented to develop village potential within the framework of regional autonomy. This strategy first identifies village potential that can be developed. After the village potential that will be developed is identified, the next step is to optimize the role of the village government in implementing the development of that potential. This is because the village government has the authority to prepare village development programs, where the potential development program can be implemented in the program prepared by the village government. Then in its implementation, the role of the Village Consultative Body as supervisor of the running of the village government also needs to be optimized so that the programs that have been prepared by the village government can run as they should. The final strategy is to involve related parties. This is important because in developing village potential, the government cannot possibly run alone without the presence of related parties. These parties must be adjusted to the potential of the village to be developed. Keywords: Village potential, village government, regional autonomy